Description Of Sleep Quality In Elderlies In The Elderly Social Rehabilitation Services Unit Of Garut Regency - Jemi, Jemi Rahmani A; Setiawan, Setiawan; Udin, Udin Rosidin (JURNAL KESEHATAN KARTIKA, 2021)
Elderlies experience various changes, both in physical and psychological aspect. Degenerative diseases is also experienced by the elderlies. This situation is a high risk and can caused poor sleep quality due to various factors. Elderlies in the elderly social rehabilitation service units are less productive during the day and sometimes do not participate in existing programs or activities.The purpose of this research was to find out the description of sleep quality in elderlies in the Elderly Social Rehabilitation Services Unit of Garut Regency. Population in this research was 75 people, and 53 people became sample taken by consecutive sampling technique. The Pittburgh Sleep Quality Index (PSQI) instrument was used to measure sleep quality. Data analysis used univariate to determine the frequency distribution of quality sleep of the elderlies. The study was conducted from April to June 2019.The results of this study found that the elderly sleep quality category in the Elderly Social Rehabilitation Service Unit of Garut Regency was dominant in the bad category (64.2%). Other results were components of sleep disorders (96.2%), sleep duration (30.2%), and activity dysfunction during the day (32.1%) were the causes of poor quality sleep in the elderly. Nurses and nursing homes are expected to know the quality of sleep in the elderly to be able to provide appropriate interventions for elderly who experience sleep disorders by maintaining an adequate sleeping environment so that the elderly can meet their sleep needs